ANALISIS PENDAPATAN DAN PROFITABILITAS INDUSTRI MEUBEL ROTAN TORA-TORA DI KOTA PALU SULAWESI TENGAH - AliminLaihi,Rustam AbdRauf,Lien damayanti, Alfit (AGROTEKBIS, 2015)
Central Sulawesi province is one of the rattan producing areas, therefore the rattan furniture industry is highly prospective for development in Palu City. One of the industries that manage rattan into various handicrafts are wicker furniture industry is Tora-Tora. It has production industry, that is quite high. However, it is still not able to properly inform its financial statements. The research objective titled analysis of revenue and profitability of the rattan furniture industry Tora-Tora in the Palu city is to determine the amount of income and profitability of rattan products industry